ASSESSMENT OF ANTINEOPLASTIC POTENTIAL OF ANNONA MURICATA LINN. IN HUMAN CANCER CELL LINES - RAJARAJAN.P,; SENTHILKUMAR.R, (International Journal of Pharma and Bio Sciences, 2015)
Annona produces a novel set of chemicals called annonaceous acetogenins, known to possess antineoplastic activity.The present study was undertaken to establish the antineoplastic potential of Annona muricata by MTT, Cell cycle (G2M) and DNA fragmentation assays. The extracts showed dose dependant growth inhibition of SCC9 (oral cancer), MCF-7 (Breast cancer), A549 (Lung Cancer) and HCT116 (Colorectal Cancer) cells. In contrast to HCT116 cells, the treated SCC9, MCF-7 and A549 cells exhibited significant cytotoxicity at a higher concentration with IC50 value of 87.8, 151.6 and 230.6 respectively. The treated SCC9 and MCF-7cells showed cell cycle arrest up to 27.97% and 19.42% respectively, at G2/M phase of the cell cycle. DNA degradation observed in both MCF-7 and SCC9 cells treated with A.muricata extract at a concentration of 320µg/ml suggest that it might induce apoptosis in both MCF-7 and SCC9 cells.